Mediating mutualisms: farm management practices and evolutionary changes in symbiont co-operation - Kiers, E; West, SA; Denison, R (2002)
1. Root symbionts (rhizobia and arbuscular mycorrhizae) are often assumed to increase agricultural productivity consistently. However, rhizobial and mycorrhizal strains vary in effectiveness, resulting in symbiotic associations that range from parasitic to mutualistic. 2. The extent to which different farming practices mediate evolutionary changes along this continuum of symbiont effectiveness is rarely discussed. However, evolutionary theory suggests that (i) fertilizer use will favour parasitism unless host-plants impose sanctions against less-effective mutualists; (ii) tillage will have contrasting effects because it decreases within-plant symbiont relatedness but also decreases the risk that mutualism will benefit future competitors; (iii) crop rotation can act as a selective agent against dominating symbiont genotypes; and (iv) rhizobial inoculation adds beneficial strains to the soil but may increase the frequency of mixed nodules that allow parasitic strains to escape host sanctions. 3. However, the existing empirical data are inadequate to test our predictions thoroughly. Changes in species composition have been documented as a result of management practices, but evolutionary changes in symbiont effectiveness are difficult to detect. Therefore, a major aim of this study was to stimulate research that will assesses directly changes in symbiotic effectiveness as a function of management practices.